Anxiety and depression prevalence and associated factors in patients with knee osteoarthritis - Feng, Qizhen; Weng, Mingjie; Yang, Xi; Zhang, Min (Frontiers in Psychiatry, 2025)
ObjectiveWith the evolving spectrum of diseases, psychological conditions such as anxiety and depression have emerged as significant global public health concerns. Notably, these psychological disorders are prevalent among patients suffering from knee osteoarthritis (KOA). Consequently, this study included 360 hospitalized patients diagnosed with KOA to examine their levels of anxiety and depression and to analyze the factors influencing these psychological states.MethodsA cohort of KOA patients from the Second Hospital of Shanxi Medical University was assessed using a general condition questionnaire, European five-dimensional health status scale (EQ5D), Western Ontario and McMaster University Osteoarthritis (WOMAC), Social Support Rating Scale (SSRS), and Hospital Anxiety and Depression Scale (HADS). Logistic regression analysis was employed to identify the factors affecting anxiety and depression.ResultsAmong 360 patients with KOA, 28.06% experienced anxiety, and 30.27% experienced depression. Multivariate logistic regression analysis showed that lower BMI, QOL, and utilization of social support scores are risk factors for anxiety and depression in KOA patients (P<0.05). Additionally, in patients with KOA, younger age, lower subjective support, and higher scores in function and daily activities emerged as significant risk factors for depression (P<0.05).ConclusionAnxiety and depression in patients with KOA warrant significant attention due to their impact on overall well-being. The factors influencing these mental health conditions are multidimensional. In clinical practice, it is essential to integrate these various influencing factors to develop targeted mental health care services. By doing so, healthcare providers can enhance the overall mental health and QOL for individuals suffering from KOA.